Análisis psicométricos de la escala de impulsividad UPPS-P para niños y adolescentes mediante el modelo politómico de Rasch - Garrido, Sebastian Jesús (2023)
The UPPS-P scale is widely used to assess impulsivity. For this reason, the psychometric properties of the extensive version of UPPS-P were analyzed from the Rasch polytomous model. Eight hundred Argentine adolescents aged 12 to 18 years participated in the study. As a result, it was found that the dimensions of the UPPS-P presented an adequate fit to the Rasch model, adequate levels in the Person Separation Index (PSI), some items with local dependence and an adequate level of unidimensionality. It is concluded that the scale is a valid instrument to assess impulsivity in adolescents; therefore, a conversion table with interval scores is presented to increase the measurement precision of the instrument.